Acute Effects of Reverse Kinesio Taping on Anaerobic Performance in Healthy Subjects: A pilot study - Dogan, Erol; Erail, Serhat; Mayda, Muhammet Hakan; Karaduman, Emre; Yilmaz, Ali Kerim; Yuceloglu Keskin, Deniz Ozge; Ermis, Egemen (Progress in Nutrition, 2021)
Study Objectives: This study aimed to determine whether the Kinesio tape (KT) application through reverse taping on the quadriceps (Q) and hamstring (H) muscles have any effect on anaerobic power (AP). Methods: Sixteen healthy males were included in the study voluntarily. Muscle facilitation and muscle inhibition techniques were performed on the Q and H muscles of both the right and left sides by applying KT in the reverse direction, and AP parameters were measured using a Wingate ergometer. In trial 1 (Baseline), KT was not applied to the participants. In trial 2 (KT), the muscle facilitation technique was applied on the vastus medialis muscle in the Q of both legs, and the muscle inhibition technique was applied on the biceps femoris and semimembranosus muscles in the H, and AP performances of the participants were taken. The SPSS 22.0 software was used for statistical analysis. Paired sample t-test was used to analyze the differences between trials. Results: KT gave higher values than Baseline with regards to peak power, relative peak power, average power, and relative average power (p < 0.05). In addition, as a result of the KT application, there were minor improvements in minimum power, relative minimum peak power, power drop, and peak power %. However, these differences were not statistically significant (p > 0.05). Conclusions: It was observed that KT applied in the reverse direction on the Q and H muscle groups had a positive effect on AP. It was considered that this effect associated with the reverse KT application stemmed from the different tensions that decreased the neuronal threshold, which in turn ensured faster and easier stimulation of motor units and increased the muscle reflex, leading to a positive effect on AP.